Profile and Frequency of One Hundred Ankle Osteoarthritis Cases in an Indonesian Tertiary Hospital - Muhammad Farhan Ibrahim; Kurnia Wahyudi; Raden Andri Primadhi (Majalah Kedokteran Bandung, 2022)
Osteoarthritis is one of the most common cases in orthopedics and traumatology clinic. Ankle osteoarthritis is less common than osteoarthritis of hip and knee. Limited data and literature resulted in suboptimal treatment strategy. The purpose of this study was to describe the profile and frequency of ankle osteoarthritis at Dr. Hasan Sadikin General Hospital Bandung, a tertiary referral hospital in Indonesia. A cross-sectional descriptive observational study was conducted on all patients diagnosed with ankle osteoarthritis enrolled in the medical record database at Dr. Hasan Sadikin General Hospital Bandung, Indonesia in November 2020–November 2021. Results showed that the majority of the patients were female (52%), aged ≥60 years old (44%), graduated from senior high school education (56%), and housewives (30%). The 100 patients were proportionally distributed with most of them were categorized as suffering from secondary osteoarthritis with post-trauma predominance. From the perspective of body mass index, 85% patients were classified as above normal. As many as 76% of patients presented to the hospital in an advanced stage. With the high rate of posttraumatic ankle osteoarthritis, concerns should be given more to the ankle trauma management, as well as to the population with high body mass index. Increased health promotion for general population and health care providers is also needed to reduce the tendency of late presentation at the health care facility.